2015
DOI: 10.1111/jace.13487
|View full text |Cite
|
Sign up to set email alerts
|

Slag Resistance Mechanism of Lightweight Microporous Corundum Aggregate

Abstract: The microstructures of the reaction interfaces between slag and corundum aggregates, microporous corundum produced in the laboratory and tabular corundum were observed after slag resistance experiments, and their associated slag resistance mechanisms were investigated. A continuous isolation layer was observed around the microporous corundum, which showed a significantly better slag resistance than tabular corundum. The formation of columnar crystals of CaAl 12 O 19 (CA 6 ) and CaAl 4 O 7 (CA 2 ) in the isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The solute concentration around small particles is greater than that around large particles; thereby, solute atoms will diffuse from small crystals to large crystals, which will result in the dissolution of small particles and growth of large particles. Therefore, average particle size will increase [13]. On the other hand, the ZrO 2 particles reacted with the gas mixture in the incinerator under the condition of high temperature, which results in the decrease of ZrO 2 .…”
Section: Chemical and Mineralogical Compositionmentioning
confidence: 95%
“…The solute concentration around small particles is greater than that around large particles; thereby, solute atoms will diffuse from small crystals to large crystals, which will result in the dissolution of small particles and growth of large particles. Therefore, average particle size will increase [13]. On the other hand, the ZrO 2 particles reacted with the gas mixture in the incinerator under the condition of high temperature, which results in the decrease of ZrO 2 .…”
Section: Chemical and Mineralogical Compositionmentioning
confidence: 95%
“…For A sample with a q-value 0.25, the large pores with a size > 7 µm is actually the cracks between matrix and aggregates. Since the dissolution of lightweight microporous alumina into slag is difficult [19], the total flux of refractory component dissolved into slag in sample A is the half as that of sample B theoretically. That means the slag viscosity in sample A increased relatively more slowly.…”
Section: Slag Penetrationmentioning
confidence: 99%
“…Through the carbothermal reduction of MgO, Yin et al fabricated lightweight corundum‐spinel refractory material with an apparent porosity of approximately 30% . Based on the characteristic of superplasticity, lightweight Al 2 O 3 ‐MgAl 2 O 4 refractory with a closed porosity of 16% and pore size of 10 μm was obtained by Yuan et al Fu et al fabricated lightweight alumina containing microscale intracrystalline pores and investigated its slag corrosion behavior . They pointed out that an isolation layer formed on the surface of the lightweight alumina during a slag corrosion test, converting the direct dissolution of lightweight alumina into indirect dissolution, meaning that the lightweight alumina exhibited guaranteed slag corrosion .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the characteristic of superplasticity, lightweight Al 2 O 3 ‐MgAl 2 O 4 refractory with a closed porosity of 16% and pore size of 10 μm was obtained by Yuan et al Fu et al fabricated lightweight alumina containing microscale intracrystalline pores and investigated its slag corrosion behavior . They pointed out that an isolation layer formed on the surface of the lightweight alumina during a slag corrosion test, converting the direct dissolution of lightweight alumina into indirect dissolution, meaning that the lightweight alumina exhibited guaranteed slag corrosion . However, further analysis revealed that the formation of a continuous isolation layer does not always occur in situ when lightweight alumina reacts with different molten slags .…”
Section: Introductionmentioning
confidence: 99%